A computational analysis of the time-variant structural response of the deck of a reinforced concrete road bridge due to corrosion of reinforcing steel - Banerjee, Soumendra; Sengupta, Amlan K. (Journal of Structural Engineering, 2024)
Corrosion of the reinforcing bars is one of the primary reasons for the deterioration of reinforced concrete bridges near the coast. There is a need for improved understanding and modelling of the influence of corrosion on the structural performance of such a bridge. The present paper provides a methodology to analyse the effect of corrosion on the strength and stiffness of the slab-and-girder deck of a road bridge. A three dimensional finite element model of a typical medium span deck of an existing bridge was developed as per the as-built drawings. The vehicular loadings were as per the recommendations of The Indian Roads Congress (IRC) specifications and the design rating of the bridge. The model was also simulated for a static proof loading using test vehicles, and for a dynamic loading generated by a shaker. Based on the corrosion due to chloride ions, a time-dependent reduction in the area of flexural reinforcement near the soffits of the girders, was considered in the model. The nonlinear effects of creep, cracking and spalling of concrete were also incorporated in the model with non-prismatic section properties and their stagewise variations. From the analysis of the time-variant response of the deck, it was observed that due to corrosion, the allowable moment capacity of a girder falls below the demand under rated service loads within the target service life of the bridge. However, as compared to creep, the effect of corrosion on the stiffness of the deck is not substantial to be accurately measured by a conventional sensor. The procedure of the computational analysis adopted in the present paper can be used by the practicing professionals for assessing longer span decks.